Interstrain Cooperation in Meningococcal Biofilms: Role of Autotransporters NalP and AutA - Pérez-Ortega, Jesús; Rodríguez, Antonio; Ribes, Eduardo; Tommassen, Jan; Arenas, Jesús (Frontiers in Microbiology, 2017)
Neisseria meningitidis (Nm) and Neisseria lactamica (Nl) are commensal bacteria that live in the human nasopharynx, where they form microcolonies. In contrast to Nl, Nm occasionally causes blood and/or meningitis infection with often fatal consequences. Here, we studied interactions between neisserial strains during biofilm formation. Fluorescent strains were engineered and analysed for growth in single- and dual-strain biofilms with confocal laser-scanning microscopy. Different strains of diverse Neisseria species formed microcolonies of different sizes and morphologies. Pair-wise combinations of two invasive Nm strains and one Nm carrier isolate showed that these strains can coexist in spite of the fact that they produce toxins to combat congeners. This lack of competition was even observed when the biofilms were formed under nutrient limitation and can be explained by the observation that the separate microcolonies within mixed biofilms are mostly lineage specific. However, these microcolonies showed different levels of interaction. The coexistence of two strains was also observed in mixed biofilms of Nm and Nl strains. Inactivation of the autotransporter NalP, which prevents the release of the heparin-binding antigen NHBA and the α-peptide of IgA protease from the cell surface, and/or the production of autotransporter AutA increased interactions between microcolonies, as evidenced by close contacts between microcolonies on the substratum. Qualitative and quantitative analysis revealed an altered spatial distribution of each strain in mixed biofilms with consequences for the biomass, biofilm architecture and bacterial viability depending on the synthesis of NalP and AutA, the expression of which is prone to phase variation. Being in a consortium resulted in some cases in commensalism and cooperative behaviour, which promoted attachment to the substratum or increased survival, possibly as result of the shared use of the biofilm matrix. We hypothesize that Nm strains can cooperate during host colonization, but, possibly, the different capacities of the microcolonies of each strain to resist the host’s defences limits the long-term coexistence of strains in the host.